A nanoporous catalyst for hydrogen production by methanol steam reforming, preparation method and application thereof

By adding strontium, thulium and ytterbium to the copper-based catalyst and using a specific adhesive to form a nanoporous body structure, the existing catalysts have solved the problems of low hydrogen production efficiency, poor stability and high energy consumption, and achieved efficient, stable and low-energy-consuming methanol water vapor reforming and hydrogen production reaction.

CN119746874APending Publication Date: 2025-04-04GUANGZHOU ANSAI CHEM IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411853223.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the hydrogen production process of methanol steam reforming, existing copper-based catalysts have low hydrogen production efficiency, excessive copper content leads to poor stability, and high applicable temperature leads to high energy consumption.

Method used

The structure of a nanoporous catalyst is adopted, and the refinement and dispersion of the active components of the catalyst is promoted by the addition of strontium, thulium and ytterbium, and combined with polyvinyl alcohol PVA, polyacrylamide PAM or sodium polyacrylate as the binder to form a carbon framework to improve the structural strength and stability of the catalyst.

Benefits of technology

It significantly improves methanol conversion and hydrogen selectivity, reduces the selectivity to CO, extends the service life of the catalyst, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191105320000061
    Figure BDA0005191105320000061
  • Figure BDA0005191105320000071
    Figure BDA0005191105320000071
Patent Text Reader

Abstract

The present invention discloses a nanoporous catalyst for hydrogen production by methanol steam reforming, a preparation method thereof and an application thereof. The nanoporous catalyst for hydrogen production by methanol steam reforming has a structure of: Cu a Al b Zn c Sr d Tm e Yb f CO g , wherein the value of a is 0.5-1, the value of b is 1.5-2.8, the value of c is 1-1.2, the value of d is 0.003-0.005, the value of e is 0.001-0.002, the value of f is 0.001-0.002, and the value of g is 3.7-5.1. The nanoporous catalyst for hydrogen production by methanol steam reforming of the present invention has high porosity, high catalytic activity, and short required activation time; mild reaction conditions, low energy consumption, improved methanol conversion rate and hydrogen selectivity, and reduced selectivity for CO; on the basis of reducing copper content, the catalytic activity is ensured, and the strength is high, the stability is good, and the service life of the catalyst is significantly extended; the preparation process is simple and easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanoporous catalyst for producing hydrogen through methanol steam reforming, a preparation method and application thereof, and belongs to the technical field of producing hydrogen through methanol steam reforming. Background Art

[0002] Hydrogen is a clean energy source with high efficiency. In recent years, it has broad development prospects in the context of addressing global climate issues and promoting the development of the global green economy.

[0003] Methanol has the advantages of being cheap and readily available, high energy density, low carbon content, and easy to transport and store. It is known as the most promising high-energy fuel. Its conversion to hydrogen production mainly includes three methods: direct cracking, steam reforming and partial oxidation reforming. Among them, methanol steam reforming to hydrogen production is the reaction with the highest hydrogen content in the conversion gas. It has the advantages of short process flow, simple equipment, low energy consumption, low cost and large hydrogen production capacity.

[0004] Copper-based catalysts have good activity and mature preparation technology. They are the most commonly used catalysts for methanol steam reforming to produce hydrogen. Compared with precious metal catalysts, Cu-based catalysts have the advantages of low cost, high low-temperature activity, and low selectivity for by-product CO.

[0005] The current industrialized Cu-Zn-Al catalyst has a relatively poor hydrogen production efficiency. In order to solve the problem of hydrogen production efficiency, some scholars have also carried out relevant research. For example, the patent with application number 201910427230.9 discloses a high-space-velocity methanol-water hydrogen production catalyst, which contains a modified cerium-zirconium oxide solid solution carrier with a mass fraction of 70% to 95% and an active component with a mass fraction of 5% to 30%; the active component includes Pt and MnO2, the mass of Pt accounts for 10% to 50% of the mass of the active component, and the mass of MnO2 accounts for 50% to 90% of the mass of the active component. This catalyst can be used under higher space velocity conditions, and the hydrogen production efficiency is significantly improved compared with the industrial copper-zinc-aluminum catalyst, but the applicable temperature of the catalyst is relatively high, which needs to reach above 400°C, which will lead to high energy consumption of the catalyst operation and high selectivity for CO.

[0006] At the same time, most of the existing copper-based catalysts have a copper oxide content greater than 50%. Too high a copper content in the catalyst will lead to problems such as poor stability. If the copper content in the catalyst is directly reduced, the activity of the catalyst will decrease. Therefore, how to reduce the copper content without affecting the activity of the catalyst has become a difficulty in the existing technology. Summary of the invention

[0007] The present invention provides a nanoporous catalyst for hydrogen production by methanol steam reforming, a preparation method and application thereof. The present invention improves methanol conversion rate and hydrogen selectivity, and simultaneously improves the use stability of the catalyst.

[0008] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0009] A nanoporous catalyst for hydrogen production by methanol steam reforming, having the structure of: Cu a Al b Zn c Sr d Tm e Yb f CO g , where the value of a is 0.5-1, the value of b is 1.5-2.8, the value of c is 1-1.2, the value of d is 0.003-0.005, the value of e is 0.001-0.002, the value of f is 0.001-0.002, and the value of g is 3.7-5.1.

[0010] The present application promotes the refinement and dispersion of the effective components of the catalyst by adding strontium, thulium and ytterbium, thereby improving the catalytic effect and promoting the improvement of the structural strength and the stability of use.

[0011] The above structure shows the structure of the catalyst effective component.

[0012] Existing catalysts have low structural strength, are fragile, have relatively low utilization rates, and have poor stability in use. Generally, they will show obvious attenuation after 200 hours of use. However, the present application effectively solves the above problems and significantly prolongs the service life of the catalyst by improving the selection of raw material components and the preparation process.

[0013] The raw materials used for the nanoporous catalyst for hydrogen production by methanol steam reforming include copper oxide, zinc oxide, aluminum oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder.

[0014] In order to ensure catalytic performance, the molar ratio of the above copper oxide, aluminum oxide, zinc oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder is (0.5-1):(1.5-2.8):(1-1.2):(0.003-0.005):(0.001-0.002):(0.001-0.002):1.

[0015] A method for preparing the nanoporous catalyst for hydrogen production by methanol steam reforming as claimed in claim 1, comprising mixing copper oxide, zinc oxide, aluminum oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder to obtain a solid material; mixing the solid material, a binder and water, extruding and granulating, and then calcining at 800-1200°C under inert gas protection for 5-8h to obtain the nanoporous catalyst for hydrogen production by methanol steam reforming.

[0016] When the binder is calcined, a carbon skeleton is formed. The active ingredients are integrated with the carbon skeleton and are evenly dispersed on the surface of the carbon skeleton.

[0017] There are many types of existing adhesives. In addition to bonding, the present application also needs to ensure that porous nanomaterials are obtained during calcination. After repeated research and development, the inventors found that when the adhesive is at least one of polyvinyl alcohol PVA, polyacrylamide PAM or sodium polyacrylate, it can effectively ensure the dispersibility of the material and avoid problems such as agglomeration. During calcination, it forms an integrated structure with the effective components and obtains a porous material. While ensuring strength, it also effectively increases the surface area and enhances the catalytic effect.

[0018] More preferably, the mass ratio of polyvinyl alcohol PVA, polyacrylamide PAM and sodium polyacrylate is 10:(1-2):(1-2).

[0019] The polyvinyl alcohol PVA is preferably polyvinyl alcohol PVA1788.

[0020] The polyacrylamide PAM is preferably polyacrylamide PAM3530.

[0021] The average molecular weight of the sodium polyacrylate is 4-5 million.

[0022] During preparation, in order to improve the uniformity of mixing, the binder and water are first mixed to obtain a binder solution with a concentration of 2-10%, and then the solid material is mixed with the binder solution and extruded into granules.

[0023] The purity of raw materials not specifically stated in this application was analytically pure.

[0024] In order to improve the dispersibility of the effective ingredients, the particle sizes of the copper oxide, aluminum oxide, zinc oxide and carbon powder are all 10-100 nm.

[0025] The method of using the above-mentioned nanoporous catalyst for hydrogen production by methanol steam reforming to produce hydrogen by methanol steam reforming comprises the following steps:

[0026] 1) Activation: The nanoporous catalyst is reduced with hydrogen at 200-240° C. for 2-4 hours to complete the activation;

[0027] 2) In the methanol steam reforming hydrogen production reaction, the mass ratio of methanol to steam is (1.70-1.75):1, the reaction temperature is 200-210℃, the reaction pressure is 0.1-0.2MPa, and the space velocity is 1-2h -1 .

[0028] This application regards a conversion rate greater than 99.999% as 100% conversion.

[0029] The technologies not mentioned in the present invention are all referred to the prior art.

[0030] The nanoporous catalyst for hydrogen production by methanol steam reforming of the present invention has high porosity, high catalytic activity and short activation time; mild reaction conditions and low energy consumption, and improves methanol conversion rate and hydrogen selectivity, while reducing CO selectivity; on the basis of reducing copper content, the catalytic activity is ensured, and the catalyst has high strength and good stability, which significantly prolongs the service life of the catalyst; the preparation process is simple and easy to operate. DETAILED DESCRIPTION

[0031] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0032] Example 1

[0033] Preparation of CuAl2ZnSr 0.004 Tm 0.002 Yb 0.002 CO 5.01 :

[0034] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.41 g of strontium oxide, 0.77 g of thulium oxide, 0.79 g of ytterbium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of strontium oxide, thulium oxide and ytterbium oxide is 200 nm;

[0035] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0036] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0037] Comparative Example 1

[0038] The difference from Example 1 is that the carbon powder is omitted, and the rest is the same as Example 1. The specific preparation process is as follows:

[0039] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.41 g of strontium oxide, 0.77 g of thulium oxide and 0.79 g of ytterbium oxide are mixed to obtain a solid material; the particle size of copper oxide and zinc oxide is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of strontium oxide, thulium oxide and ytterbium oxide is 200 nm;

[0040] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0041] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0042] Comparative Example 2

[0043] The difference from Example 1 is that ytterbium oxide is omitted, and the rest is the same as Example 1. The specific preparation process is as follows:

[0044] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.41 g of strontium oxide, 0.77 g of thulium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of strontium oxide and thulium oxide is 200 nm;

[0045] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0046] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0047] Comparative Example 3

[0048] The difference from Example 1 is that thulium oxide is omitted, and the rest is the same as Example 1. The specific preparation process is as follows:

[0049] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.41 g of strontium oxide, 0.79 g of ytterbium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of strontium oxide and ytterbium oxide is 200 nm;

[0050] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0051] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0052] Comparative Example 4

[0053] The difference from Example 1 is that strontium oxide is omitted, and the rest is the same as Example 1. The specific preparation process is as follows:

[0054] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.77 g of thulium oxide, 0.79 g of ytterbium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of thulium oxide and ytterbium oxide is 200 nm;

[0055] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0056] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0057] Comparative Example 5

[0058] The difference from Example 1 is that thulium oxide and ytterbium oxide are omitted, and the rest is the same as Example 1. The specific preparation process is as follows:

[0059] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.41 g of strontium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of strontium oxide is 200 nm;

[0060] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0061] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0062] Comparative Example 6

[0063] The difference from Example 1 is that strontium oxide and thulium oxide are omitted, and the rest are the same as in Example 1. The specific preparation process is as follows:

[0064] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.79 g of ytterbium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of ytterbium oxide is 200 nm;

[0065] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0066] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0067] Comparative Example 7

[0068] The difference from Example 1 is that strontium oxide and ytterbium oxide are omitted, and the rest are the same as Example 1. The specific preparation process is as follows:

[0069] 1) 8 g of copper oxide, 10.2 g of aluminum oxide, 8.1 g of zinc oxide, 0.77 g of thulium oxide and 1.2 g of carbon powder are mixed to obtain a solid material; the particle size of copper oxide, zinc oxide and carbon powder is 50 nm, the particle size of aluminum oxide is 20 nm, and the particle size of thulium oxide is 200 nm;

[0070] 2) Add 2 g of polyvinyl alcohol PVA1788 (Yifeng Chemical), 0.3 g of polyacrylamide PAM3530 (Boling) and 0.3 g of sodium polyacrylate (average molecular weight 4-5 million, MacLean) into 50 g of water and mix well to obtain an adhesive solution;

[0071] 3) 12 g of the binding liquid was added to the solid material obtained in step 1), mixed, extruded into granules (cylindrical, 5 mm in diameter, 8 mm in height), and then calcined at 1000° C. under inert gas protection for 8 h to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

[0072] BET was measured by JW-BK200A surface area analyzer, and mechanical strength was measured by particle strength tester. Catalyst activation method: The catalysts prepared in each example were reduced with hydrogen at 220°C for 3h.

[0073] Table 1 shows the physical properties of the catalysts obtained in each example.

[0074]

[0075] The catalyst performance was evaluated in a fixed bed reactor. 2 g of catalyst was weighed and placed in a reaction tube. Before the reaction, hydrogen was introduced at 220 °C for 3 h at a hydrogen flow rate of 35 ml / min, and then the temperature was reduced to 200 °C and the reaction was carried out at normal pressure. Methanol and water were fed by a constant flow pump at a mass ratio of 1.75:1 at an air velocity of 1 h -1 After being vaporized in a preheater, it is mixed with nitrogen and enters the reaction tube to react. After the reaction, the gas is first separated by a condenser, and the non-condensable gas is analyzed by gas chromatography (thermal conductivity cell detector, TDX-01 filling column). The reaction results are tested after 6h, 360h, and 720h.

[0076] Table 2 shows the catalytic performance of the catalysts obtained in each example.

[0077]

Claims

1. A nanoporous catalyst for hydrogen production by methanol steam reforming, characterized in that: Its structure is: Cu a Al b Zn c Sr d Tm e Yb f CO g , where the value of a is 0.5-1, the value of b is 1.5-2.8, the value of c is 1-1.2, the value of d is 0.003-0.005, the value of e is 0.001-0.002, the value of f is 0.001-0.002, and the value of g is 3.7-5.

1.

2. The nanoporous catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: The raw materials used include copper oxide, zinc oxide, aluminum oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder.

3. The nanoporous catalyst for hydrogen production by methanol steam reforming according to claim 2, characterized in that: The molar ratio of copper oxide, aluminum oxide, zinc oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder is (0.5-1):(1.5-2.8):(1-1.2):(0.003-0.005):(0.001-0.002):(0.001-0.002):

1.

4. A method for preparing the nanoporous catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: Copper oxide, zinc oxide, aluminum oxide, strontium oxide, thulium oxide, ytterbium oxide and carbon powder are mixed to obtain a solid material; the solid material, a binder and water are mixed, extruded into granules, and then calcined at 800-1200°C under the protection of an inert gas for 5-8 hours to obtain a nanoporous catalyst for hydrogen production by methanol steam reforming.

5. The preparation method according to claim 4, characterized in that: The adhesive is at least one of polyvinyl alcohol (PVA), polyacrylamide (PAM) or sodium polyacrylate.

6. The preparation method according to claim 5, characterized in that: The mass ratio of polyvinyl alcohol PVA, polyacrylamide PAM and sodium polyacrylate is 10:(1-2):(1-2).

7. The preparation method according to claim 5 or 6, characterized in that: The polyvinyl alcohol PVA uses polyvinyl alcohol PVA1788; the polyacrylamide PAM uses polyacrylamide PAM3530; and the average molecular weight of sodium polyacrylate is 4-5 million.

8. The preparation method according to any one of claims 4 to 6, characterized in that: Firstly, the adhesive and water are mixed to obtain an adhesive solution with a concentration of 2-10%, and then the solid material is mixed with the adhesive solution and extruded into granules.

9. The preparation method according to any one of claims 4 to 6, characterized in that: The particle sizes of copper oxide, aluminum oxide, zinc oxide and carbon powder are all 10-100 nm.

10. An application of the nanoporous catalyst for hydrogen production by methanol steam reforming according to claim 1, characterized in that: Used for methanol steam reforming to produce hydrogen, including the following steps: 1) Activation: The nanoporous catalyst is reduced with hydrogen at 200-240° C. for 2-4 hours to complete the activation; 2) In the methanol steam reforming hydrogen production reaction, the mass ratio of methanol to steam is (1.70-1.75):1, the reaction temperature is 200-210℃, the reaction pressure is 0.1-0.2MPa, and the space velocity is 1-2h -1 .

Citation Information

Patent Citations

  • High-space velocity catalyst for hydrogen production from methanol-water and preparation method and application thereof

    CN110038565A